Invasion of Europe by the western corn rootworm, Diabrotica virgifera virgifera : multiple transatlantic introductions with various reductions of genetic diversity - M. CIOSI; N. J. MILLER; K. S. KIM; R. GIORDANO; A. ESTOUP; T. GUILLEMAUD (Molecular Ecology, 2008)
The early stages of invasion involve demographic bottlenecks that may result in lower genetic variation in introduced populations as compared to source population/s. Low genetic variability may decrease the adaptive potential of such populations in their new environments. Previous population genetic studies of invasive species have reported varying levels of losses of genetic variability in comparisons of source and invasive populations. However, intraspecific comparisons are required to assess more thoroughly the repeatability of genetic consequences of colonization events. Descriptions of invasive species for which multiple introductions from a single source population have been demonstrated may be particularly informative. The western corn rootworm (WCR), Diabrotica virgifera virgifera , native to North America and invasive in Europe, offers us an opportunity to analyse multiple introduction events within a single species. We investigated within‐ and between‐population variation at eight microsatellite markers in WCR in North America and Europe to investigate the routes by which WCR was introduced into Europe, and to assess the effect of introduction events on genetic variation. We detected five independent introduction events from the northern USA into Europe. The diversity loss following these introductions differed considerably between events, suggesting substantial variation in introduction, foundation and/or establishment conditions. Genetic variability at evolutionarily neutral loci does not seem to underlie the invasive success of WCR in Europe. We also showed that the introduction of WCR into Europe resulted in the redistribution of genetic variance from the intra‐ to the interpopulational level contrary to most examples of multiple introductions.